Health equity and financial protection : streamlined analysis with ADePT software - Wagstaff, Adam (World Bank e-Library., 2011)
Two key policy goals in the health sector are equity and financial protection. New methods, data and powerful computers have led to a surge of interest in quantitative analysis that permits monitoring progress toward these objectives, and comparisons across countries. ADePT is a new computer program that streamlines and automates such work, ensuring that results are genuinely comparable and allowing them to be produced with a minimum of programming skills. This book provides a step-by-step guide to the use of ADePT for quantitative analysis of equity and financial protection in the health sect.